2010
DOI: 10.1098/rspb.2010.0022
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity reduces the effect of poor developmental conditions on fledging age in mourning doves

Abstract: Developmental plasticity can be integral in adapting organisms to the environment experienced during growth. Adaptive plastic responses may be especially important in prioritizing development in response to stress during ontogeny. To evaluate this, I examined how developmental conditions for mourning doves related to early growth and how this affected fledging age, an important life-history transition for birds. The life history of mourning doves is consistent with strong selective pressure to minimize fledgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…overall, food-restricted nestlings fledged at later ages compared with controls (due to slower overall growth), yet the food-restricted birds that prioritized wing growth over growth of other body tissues mitigated the delayed fledging effects associated with their reduced size (Miller, 2010). In both our control and food-restricted house sparrows, we observed rapid increases in tarsus length during the first week post-hatch, followed by slowed growth to day 12.…”
Section: T L Killpack and W H Karasovmentioning
confidence: 65%
See 2 more Smart Citations
“…overall, food-restricted nestlings fledged at later ages compared with controls (due to slower overall growth), yet the food-restricted birds that prioritized wing growth over growth of other body tissues mitigated the delayed fledging effects associated with their reduced size (Miller, 2010). In both our control and food-restricted house sparrows, we observed rapid increases in tarsus length during the first week post-hatch, followed by slowed growth to day 12.…”
Section: T L Killpack and W H Karasovmentioning
confidence: 65%
“…Therefore, if growth is not maintained when circulating levels of growth hormones are high, negative and permanent consequences for bird fitness and survival may result. Reduced size because of food limitation has been shown to delay fledging time (Cruz and Cruz, 1990;Searcy et al, 2004;Takenaka et al, 2005;Miller, 2010), decrease social rank (Richner et al, 1989) and decrease predicted recruitment and survival of birds in the wild . A study of mourning doves showed that,…”
Section: Maintenance Of Structural Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Condition is thought to be indicative of an animal's health and well-being and related to fitness (Peig and Green, 2009). In developing animals, condition could be an important indicator of competitive ability within the nest, maturation, and survival and recruitment following fledging (Miller, 2010;Mock et al, 2009;Searcy et al, 2004). We assessed condition using residual body mass (mass divided by tarsus length) and the scaled mass index (Peig and Green, 2009;Peig and Green, 2010).…”
Section: Nestlings -Stress Immune Morphological and Condition Measumentioning
confidence: 99%
“…Such a low weight at fledging is expected when the life history has evolved under selective pressures to minimize age at fledging. This can happen in the case of heavy predation, high parasite load, or starvation during the chick phase (Miller 2010). Crab Plover chicks have a very low parasite load (F. H. Teyefeh, pers.…”
Section: Discussionmentioning
confidence: 99%